Modelling and optimization of micro optofluidic lenses - Song, Chaolong (2012)
This paper reports the modelling and experimental results of a liquid-core liquid-cladding optofluidic lens. The lens is based on three laminar streams in a circular chamber. The stream lines and the curvature of the interface can be predicted accurately using the theory of two-dimensional dipole flow in a circularly bounded domain. The model establishes basic relations between the flow rate ratio of the core/cladding streams and the radius of curvature and consequently the focal length of the lens. Compared to a rectangular chamber, this new circular design allows the formation of a liquid-core liquid-cladding lens with perfect curvatures. The circular design allows tuning a perfect curvature ranging from the chamber radius itself to infinity. The test device with a circular lens chamber with 1 mm diameter and 50 µm height was fabricated in PDMS. The lens shape as well as the stream lines were characterized using fluorescent dye and tracing particles. Experimental results agree well with the analytical results predicted by the model.